The Principle of Good Faith In Transactional Agreements In The Community of West Seram Regency - Akyuwen, Rory Jeff; Panjaitan, Wijaya Natalia; Nabila, Syadzwina Hindun (Batulis Civil Law Review, 2023)
Introduction: In the western Seram Regency, in some contracts made by the people of Wasia and Rumahkay villages, there is an imbalance in the implementation of contracts where contracts that occur most often are oral contracts in addition to written contracts, where each contract made often does not fulfill the elements of Article 1338 of the Civil Code which contains the principle of good faith.Purposes of the Research: to find out how The Principle Of Good Faith In Transactional Agreements In The Community Of West Seram Regency.  Methods of the Research: This Study Case uses sociolegal research, which is a combination research method between doctrinal legal research methods and empirical legal research methods. Results of the Research: The consequences of the existence of the principle of bad faith in the agreement being canceled because it did not fulfill the subjective requirements in the agreement. The solution is the need for encouragement for the Village Government as a Transactional Agreement Deed Facilitator as a preventive measure to reduce the inequality of agreements. In addition, there is a need for a standardized agreement format provided by the village government to meet the transactional needs of the community.